I see London [large type] - Cleeton, Chanel (Cleeton, Chanel. International school series., 2024)
"Maggie Carpenter is a small-town Southern girl who's never been kissed. She's ready for a change..she accepts a scholarship to the International School in London, where she's suddenly mingling with the privileged offspring of diplomats and world leaders. When Maggie meets Hugh...she finds herself living the life she has always wanted...The only problem? There's someone else...Half French, half Lebanese and impossibly rich, Samir Khouri has made it clear to Maggie that despite their intense attraction, he doesn't do relationships. He's the opposite of everything she thought she wanted--a player with no interest in commitments--but she just can't keep away"--